Addressing the supply and quality of engineering graduates for the new century. - King, Robin (Australian Learning and Teaching Council, 2008)
This report examines the current state of the higher education component of the Australian engineering education system, with respect to its ability to address future needs, contextualised by assessing the implementation of outcomes of the 1996 Review of Engineering, Changing the Culture. Recommended changes to the engineering program accreditation process are judged to have been successful in driving greater emphasis on generic graduate attributes in first-degree engineering programs. The Review also stimulated improvements in curriculum design and delivery, including project, problem, and workplace-based learning, and increase emphasis on sustainability. The present study has also identified substantial and emerging strengths of many of Australia's engineering schools in the areas of research, international education, and in addressing industry-specific skills shortages though both undergraduate and postgraduate programs.